Pengaruh Pemotongan Umbi Dan Pemberian Beberapa Dosis Pupuk Npk Majemuk Terhadap Pertumbuhan Dan Hasil Tanaman Bawang Merah (Allium ascolanicum L.) - Andi Apriany Fatmawaty; Sri Ritawati; Lisa Noviyanti Said (Faculty of Agriculture, Pattimura University, 2015)
Implementation of good cultivation systems can improve onion (Allium ascalonicum L.) yield. The purpose of this study was to determine the effect of tuber cuttings and the dose of NPK fertilizer on the growth and yield of onion. The experimental design was factorial randomized block design arranged consisting of two factors. The first factor was tuber cuttings which consists of without and with ¼ and 1/3 cut; the second one was dosage of NPK fertilizer which consists of without and with 200 kg/ha; 400 kg/ha; 600 kg/ha. There are 12 combinations of treatments, each of which is repeated three times. The results showed that there was no interaction effect between tuber cutting and NPK dosages on growth and yield of onion. independent effect of tuber cuttings and NPK dosages also didn’t inflence both parameter. Tuber cuttings only increase pant height at one and two weeks after planting. Overall, cutting-quarter of the tuber could induce better fresh weight and dry weight of tubers although statistically didn’t significant.